Features of childhood in rear Siberian city during the great Patriotic War (on the example of Omsk) - M. S. Nosova (Омский научный вестник: Серия "Общество. История. Современность")
Article studies the everyday life of children during the great Patriotic war on the example of rear Siberian city. The study used a wide range of documentary sources, newspapers and oral sources to describe the main features of the daily life of children in Omsk, due to the war. Extreme organizational and pedagogical conditions of schools, increased attention to the organization of Patriotic education of children in relation to the problems of wartime, difficulties in buying or sewing clothes, as well as the lack of basic toys for children were fully manifested in Omsk and were also inherent in other rear regions of the USSR. A feature of the Omsk region was the fundamental importance of helping children in agricultural work. Urban children participated in the processing and harvesting of collective crops, replacing those who went to the front. They also worked on personal plots, made a significant contribution to the food supply of their families